PENERAPAN 3 M COVID 19 SISWA- SISWI SEKOLAH DASAR NEGERI 214 KOTA JAMBI - Indah Mawarti; Muthia Mutmainnah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2022)
ABSTRACT Introduction : (WHO) Stating that Europe has become the center of the global Corona virus pandemic, Europe has more cases and deaths from COVID 19 than China, According to WHO, at least 123 countries and regions of that number, almost 81 thousand cases are in mainland China, Italy, which is a European country that has the worst impact on the corona virus, is now recorded as the most dominant. Education that is being carried out now distance learning will reduce the risk of spreading the corona virus and according to the circular issued by the Ministry of Education and Culture, learning through online. Almost a year in Indonesia, especially in Jambi province, elementary school students are on holiday. Complaints - Complaints obtained from guardians of students appear during their child's online learning process, for example, parents have limitations or find it difficult to help with homework given by the teacher to their children, parents feel burdened. Objective: Community service activities in partnership with 214 state elementary schools with the aim that students know how to apply 3M covid-19 in the elementary school. The approach taken in this service is to solve the problems that exist in students by teaching how to wash hands, wear masks correctly and how to keep loot between fellow students. It is hoped that this activity can be applied anywhere. Methods: Implementing 3M COVID 19 for students at State Elementary School 214 Jambi City. Results: Participants who took part in community activity counseling with the title Application of 3 M Covid 19 students from 214 State Elementary Schools in Jambi City. More than half of KLS 4, 5 and 6. by 64.99%. Conclusion: students can apply directly what has been taught. one of them is how to wash hands so that they are clean and avoid covid 19 disease, practice directly putting on masks so they don't turn over and keep your distance when inside and outside the classroom. Keywords: Students, Application, 3M ABSTRAK Pendahuluan : (WHO) Menyatakan Eropa telah menjadi pusat pandemic virus Corona secara global, Eropa memiliki lebih banyak kasus dan kematian akibat COVID 19 dibanding China, Menurut WHO sedikitnya 123 negara dan wilayah jumlah tersebut, nyaris 81 ribu kasus ada diwilayah China daratan, Italia, yang merupakan Negara Eropa yang berdampak virus corona terparah, kini tercatat domminan terbanyak.pendidikan yang dilakukan sekarang pembelajaran jarak jauh akan mengurangi resiko penyebaran virus corona dan sesuai edaran yang di keluarkan oleh Kemendikbud belajar melalui daring. Hampir Satu Tahun lebih Indonesia Khususnya provinsi Jambi murid SD libur. Keluhan – Keluhan yang didapat dari wali murid bermunculan selama anaknya melakukan proses pembelajaran melalui daring misalnya orang tua mempunyai batasan atau kesulit membantu pekerjaan rumah yang diberikan oleh guru kepada anaknya, orang tua merasa terbebankan. Tujuan: Kegiatan pengabdian bermitra dengan sekolah dasar negeri 214 dengan tujuan agar siswa mengetahui bagaimana penerapan 3M covid-19 di SD tersebut. Pendekatan yang dilakukan pada pengabdian ini untuk menyelesaikan permasalahan yang ada pada siswa dengan cara mengajarkan cara mencuci tangan, memakai masker yang benar dan dan cara menjaga jarah antar sesama siswa. Diharapkan dari kegiatan ini bisa diterapkan dimanapun berada.Metode: Melakukan penerapan 3M COVID 19siswa –siswi Sekolah Dasar Negeri 214 Kota Jambi. Hasil: Peserta yang mengikuti penyuluhan kegiatan masyarakat dengan judul Penerapan 3 M Covid 19 siswa- siswi Sekolah Dasar Negeri 214 Kota Jambi. Lebih dari separuh KLS 4, 5 dan 6.sebesar 64.99%. Kesimpulan : siswa bisa menerapkan secara langsung apa yang telah diajarkan. salah satunya bagaimana langkah – langkah mencuci tangan supaya bersih dan terhindar dari penyakit covid 19, mempraktekan secara langsung memasang masker agar tidak terbalik dan menjaga jarak pada saat di dalam dan diluar kls. Kata kunci: Siswa,Penerapan, 3M